The Effect Of Corporate Social Responsibility On Word Of Mouth With Trust And Corporate Reputation As Intervening Variable - Supriyatno, Alif (Jurnal Manajemen Bisnis, 2018)
This study aims to determine the effect of corporate social responsibility on word of mouth with trust and corporate reputation as mediating variable, study on Hero Supermarket customer in Yogyakarta.The sampling method used in this study is purposive sampling. The number of samples in this study is 130 customers of Hero Supermarket in the last 6 months. Data were collected using questionnaire, analyzed using structural equation modeling with Amos vers. 22.0 software. The result of this study proves that corporate social responsibility has positive and significant effect on trust, corporate social responsibility has positive and significant effect on corporate reputation, corporate social responsibility has no significant effect on word of mouth, trust has no significant effect on word of mouth, corporate reputation has positive and significant effect on word of mouth, trust could not mediate the effect of corporate social responsibility on word of mouth and corporate social responsibility indirectly has higher effect on word of mouth through corporate reputation.